Multiparameter analysis of small non-flying mammals’ response to forest restoration post-bauxite mining in eastern Amazonia - Halícia Celeste; Paula Cristina Rodrigues Almeida-Maués; Alexandra Maria Ramos Bezerra; Maria Aparecida Lopes; Marlúcia Bonifácio Martins; Ana Cristina Mendes-Oliveira (PLoS ONE, 2025)
Bauxite mining has been caused severe changes in the natural ecosystems of the Amazon, but the restoration of these areas is mandatory by federal law in Brazil. The recolonization of fauna is crucial to establishing the ecological functions of recovering forests, and the small nonflying mammals can stand out in this process. Assessing taxonomic and functional diversity parameters, we demonstrated that in the early stages of forest recovery post-bauxite mining, between 6 and 11 years, it is possible to restore approximately 45% of the richness of small non-flying mammal species from the original habitats, that in this case were altered Primary Forests. However, the species richness parameter alone does not reflect the recovery of taxonomic or functional diversity at this stage of forest succession. Although 34.8% of the species composition is shared between the Altered Primary Forest and Forest Areas in Restoration, the abundance distribution per species is less balanced in the latter habitat. The areas did not exhibit significant difference between the functional divergence and functional evenness of ecological functions performed by small nonflying mammals; however, they present differences in terms of the functional richness. We also observed that some functional traits of species, such as larger body mass, are more closely related to the structural characteristics of the Primary Forest, such as high basal area values, litter and percentage forest cover. In the forest recovery areas, we observed a predominance of terrestrial species and those with granivorous and insectivorous diets. Furthermore, our results highlight the importance of applying different taxonomic and functional diversity parameters to understand better the fauna recovery patterns in degraded areas undergoing restoration.